The bibliometric life of resource-rich Africa: Origins, evolution and influence of the relevant literature - Mendonça, S. (Africa and the PALOP (Portuguese speaking African countries): Natural resources and development, 2013)
The scarcity and the geo-politics of control over strategic resources has motivated debate and research ever since the rise of fossil-fuel enabled international economy. Indeed, the access to raw materials and other key inputs has remained a vital part of the modern technology-based economy. The paper reports the results of a bibliometric analysis of the scholarly literature on natural resources in Africa. This paper applies this approach to map and measure the emergence and dynamics of this literature, as published in international scholarly journals. A number of theoretical and empirical strands of research are identified. The results reveal the main academic journals involved in the discussion of this theme, the countries with most scientific production, the methodological tool employed, and the most focused topics. These findings can be useful for underpinning future streams of study.